ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS KARYAWAN - Pekei, Firda Sevly Aweida; Setiawan, Margono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Gaps found in past studies regarding employee loyalty have urged more researches. Therefore, this descriptive quantitative study aims to analyze the partial and simultaneous effects of compensation, workplace environment, leadership, job stress, and organization communication on the loyalty of employees working at the Sharia-Compliant Business Unit of PT. Bank Sinarmas in Malang. Using census sampling, all members of the population, i.e. employees working in the unit, were selected as the sample. This study finds that compensation, workplace environment, leadership, job stress, and organization communication partially and simultaneously influence employee loyalty. Future researches are advised to include more variables with higher relevance in studying different companies.